Из Именного указателя к «Записным книжкам» Ахматовой [From an Index to Anna Akhmatova’s Notebooks] - Timenchik, Roman (Slavica Revalensia, 2020)
This article is yet another installment in the series of Roman Timenchik’s annotations to Anna Akhmatova’s Notebooks (see also two previous volumes of Slavica Revalensia). This particular installment concerns the following persons mentioned in Akhmatova’s notes: Sam N. Driver (1929—2003), Tat’iana Gndich (1907—1976), Alexander Golovin (1863—1930), Ernest Hemingway (1899—1961), and Jovan Jovanović Zmaj (1833—1904). Among other things, it includes the first publication of the surviving fragments of the very first English translation of Akhmatova’s Poema bez geroia (A Poem without A Hero) made by Tat’iana Gnedich (in whose translation most Russians read Don Juan by Lord Byron).